1994
DOI: 10.2514/3.23801
|View full text |Cite
|
Sign up to set email alerts
|

Application of dynamical systems theory to nonlinear combustion instabilities

Abstract: Two important approximations have been incorporated in much of the work with approximate analysis of unsteady motions in combustion chambers: truncation of the series expansion to a finite number of modes, and time averaging. A major purpose of the analysis reported in this paper has been to investigate the limitations of those approximations. In particular two fundamental problems of nonlinear behavior are discussed: the conditions under which stable limit cycles of a linearly unstable system may exist; and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Substitution into the conservation and state equations yields the governing equations for the 3 fluctuating quantities. Spatial averaging is applied to those equations followed by a modal expansion of the unsteady pressure and velocity fields in order to get a reduced order model of the system.…”
Section: Instabilitiesmentioning
confidence: 99%
“…Substitution into the conservation and state equations yields the governing equations for the 3 fluctuating quantities. Spatial averaging is applied to those equations followed by a modal expansion of the unsteady pressure and velocity fields in order to get a reduced order model of the system.…”
Section: Instabilitiesmentioning
confidence: 99%
“…Common terminology used to describe this type of oscillationincludestriggeredinstability, hard excitation, and subcritical bifurcation. Previous works, for example, Yang et al, 1 Paparizos and Culick, 2 and Jahnke and Culick, 3 have convincinglyshown that nonlineargasdynamicsalone does not contain the possibility of pulsed oscillations. Part of the purpose of the present investigation is to determine if noise processes could be responsible for the occurrence of pulsed oscillations.…”
mentioning
confidence: 99%
“…This information is usually represented in the form of a plot of steady state values (peak amplitude in case of a limit cycle) against a suitable parameter in a bifurcation diagram. For longitudinal acoustic modes in a combustion chamber of uniform cross section, Jahnke and Culick [18] showed that results from a two-mode approximation were qualitatively dissimilar to those from a four-or six-mode approximation. However, they could draw no conclusion about the number of acoustic modes that need to be retained in their analysis, nor did their computations with second order gasdynamics alone display triggered limit cycles.…”
Section: Introductionmentioning
confidence: 99%
“…However, they could draw no conclusion about the number of acoustic modes that need to be retained in their analysis, nor did their computations with second order gasdynamics alone display triggered limit cycles. Culick et al [19] extended the work in [18] by including the nonlinear combustion model of Levine and Baum [17] in addition to the second order gasdynamic nonlinearities. They confirmed that the nonlinear velocity coupling term in the Levine-Baum model did induce triggered limit cycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation